Angiotensin converting enzyme I/D polymorphism and sarcoidosis risk - Yang, H.; Mo, T.; Nie, W.; Li, B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: This meta-analysis investigates the associations of angiotensin-converting enzyme (ACE) polymorphism and risk of sarcoidosis. Material and Method: Two reviewers independently searched three databases including PubMed, EMBASE, and Cochrane database to identify published studies. Full texts of the selected studies were accessed and related data was extracted using a standardized data extraction form. Results: A total of 18 studies contained a total of 1626 patients with sarcoidosis in case group and 2465 healthy controls in control group. Results of the current meta-analysis revealed that ACE DD genotype was associated with a significantly increased risk of sarcoidosis (OR=1.21; 95%CI, 1.06–1.38; I2=48%). In the race subgroup analysis, Asians with ACE DD genotype showed no significant increased risk of sarcoidosis (OR=1.37; 95%CI, 0.94–1.99; I2=78%). Caucasians with ACE DD genotype had an increased sarcoidosis risk (OR=1.16; 95%CI, 1.01–1.36; I2=24%). Conclusions: Our meta-analysis indicated that the ACE DD genotype correlated with an increased risk of sarcoidosis. (Sarcoidosis Vasc Diffuse Lung Dis 205; 32: 284-288)